Employment and Industrialization: Comment - Cohen, Benjamin I.; Leff, Nathaniel H. (Quarterly Journal of Economics, 1967)
Journal Article Employment and Industrialization: Comment Get access Benjamin I. Cohen, Benjamin I. Cohen Harvard University Search for other works by this author on: Oxford Academic Google Scholar Nathaniel H. Leff Nathaniel H. Leff Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 81, Issue 1, February 1967, Pages 162–164, https://doi.org/10.2307/1879682 Published: 01 February 1967